2004
DOI: 10.1134/1.1764884
|View full text |Cite
|
Sign up to set email alerts
|

A hard X-ray survey of the Galactic-Center region with the IBIS telescope of the INTEGRAL observatory: A catalog of sources

Abstract: During the period Aug.23-Sept.24 2003, the INTEGRAL observatory performed an ultra deep survey of the Galactic Center region with a record sensitivity at energies higher than 20 keV. We have analized images of the Galactic Center region obtained with the ISGRI detector of the IBIS telescope (15-200 keV) and present here a catalog of detected sources. In total, 60 sources with a flux higher than 1.5 mCrab have been detected. 44 of them were earlier identified as Galactic binary systems, 3 are extragalactic obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 17 publications
3
140
1
Order By: Relevance
“…Hard X-ray emission has been detected from three AXPs with INTEGRAL: 1E 1841-045 [35], 4U 0142+61 [11] and 1RXS J170849-400910 [42]. The presence of pulsations seen with RXTE up to ∼200 keV in 1E 1841-045 ( [19]) proofs that the hard Xray emission originates from the AXP and not from the associated supernova remnant Kes 73.…”
Section: Comparison With the Anomalous X-ray Pulsarsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hard X-ray emission has been detected from three AXPs with INTEGRAL: 1E 1841-045 [35], 4U 0142+61 [11] and 1RXS J170849-400910 [42]. The presence of pulsations seen with RXTE up to ∼200 keV in 1E 1841-045 ( [19]) proofs that the hard Xray emission originates from the AXP and not from the associated supernova remnant Kes 73.…”
Section: Comparison With the Anomalous X-ray Pulsarsmentioning
confidence: 97%
“…By adding these results to the ones obtained for the ISGRI total spectrum, one can derive the total energy output during the whole event, which is 1.2×10 −4 erg cm −2 . This corresponds to 3.25×10 42 These results can be explained in the framework of a recent evolution of the magnetar model, where Lyutikov (2003) explains SGR bursts as generated by loss of magnetic equilibrium in the magnetosphere, in close analogy to solar flares: new current-carrying magnetic flux tubes rise continuously into the magnetosphere, driven by the deformations of the neutron star crust. This in turn generates an increasingly complicated magnetic field structure, which at some point becomes unstable to resistive reconnection.…”
Section: Short Burstsmentioning
confidence: 98%
See 1 more Smart Citation
“…It contains more information on variability over long time scale in the hard X-ray band than for example the ROSAT all-sky survey catalogues, the ASCA 0.7-10 keV (Sugizaki et al 2001) and the first three INTEGRAL-IBIS low galactic latitude surveys (Bird et al 2004;Bird et al 2006;Revnivtsev et al 2004) and the high galactic latitude survey of the Swift-BAT (Markwardt et al 2005), and comparable with the last INTEGRAL-IBIS survey (Bird et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Kuiper et al (2004) showed unambiguously that the hard X-rays originated from the AXP by extracting a pulsed hard X-ray signal from the source using archival RXTE data. After INTEGRAL discovered hard X-rays from two other AXP locations, namely from 1RXS J1708-4009 (Revnivtsev et al 2004) and 4U 0142+61 (den Hartog et al 2004), Kuiper et al (2006) also showed for these and for a fourth AXP (1E 2259+586) pulsed hard X-ray emission using archival RXTE data. That means that presently already for 4 of the 7 established AXPs hard X-ray emission has been detected and this can now be considered to be a common characteristic, which is not yet understood.…”
Section: Introductionmentioning
confidence: 99%